THE SCIENCES OF MAN: MULTI-, INTER-, TRANS., POLI-, POST DISCIPLINARITY - Portugal Bernedo, Franz (2009)
This text questions the problems and solutions derived ttom the atomization and increasingspecialization of the sciences of man. This fact had led to multidisciplinary,interdisdplinary, transdisciplinary, and postdisciplinary conceptions as a way of solving this fragmentaüon and reaching an integral comprehension of reality, a propasa! caughtitself inro a disciplinary conception of reality. Sorne have tried to go far beyond andbacked the unification of the hurnan sciences, displadng the borders, the centers ofgravity and the traditional problems, and have propitiated the abandonment of the "nationalistic"spirit of each one of them, ro include all the sdences of man. Neverthelesst_he problem is more complexas far as it is the paradigm of the human sciences what isin debate. Iris necessary not only to rethink them but to "think them in" as Wallersteinpropases.